ANALISIS KEMAMPUAN BERBICARA MAHASISWA MELALUI MEDIA YOUTUBE - Tati Sri Uswati; Rahayu Pristiwati; Veni Nurpadillah (CAKRAWALA LINGUISTA, 2022)
This research, entitled Analysis of Students' Speaking Ability through Youtube Media, aims to see students' speaking skills by utilizing social media, especially YouTube in the lecture process. Lecturers initiate to use youtube media, this aims to create an atmosphere that allows students to practice directly using spoken language, as well as a form of motivation so that students can improve their speaking skills. This research is qualitative research. The source of the data in this study is a video uploaded via YouTube as a result of the civil service course assignment. The results of this study The use of YouTube media in lecture activities, especially in civility courses, can motivate students to improve speaking skills. Currently, the influence of mass media, especially YouTube, on students is quite large. This can be seen from several student recognitions, namely they become more enthusiastic and creative in doing assignments.